Smes And The Challenge Of Internationalization: Challenges Of Resistance And Support Strategies - Bouri, Nassima (جامعة الوادي - University of Eloued, 2019)
The majority of analyzes on the Algerian economy evoke the increasingly important role played by SMEs in the economic growth of the country. These continue to be the source of most new jobs, improving economic competitiveness. As an organized economic institution, its growth will depend on its ability to withstand the movements of an uncertain economic environment that weakens it. Its survival is a function of resistance to the considerable strengths and opportunities of competition and to intercept new local and international markets. La majorité des analyses sur l’économie algérienne évoquent le rôle de plus en plus important joué par les PME dans la croissance économique du pays. Elles continuent à être à la source de la plus grande partie des nouveaux emplois, de l’amélioration de la compétitivité économique. En tant qu’une institution économique organisée, sa croissance dépendra de sa capacité à résister aux mouvements d’un environnement économique incertain qui la fragilise. Sa survie est une fonction de résistance face aux atouts et aux opportunités considérables de la concurrence et à intercepter de nouveaux marchés locaux et internationaux
مقال
Keywords: Key words: SMEs, internationalization, growth, competitiveness, globalization, export, SME support structures. Jel Classification: L32, 019, F43, D41, F23, F13, G21.